On the relation between plasma power and aging treatment in the production of thin aluminum zirconium foils by magnetron sputtering: Einfluss von Plasmaleistung und Alterung auf die Fertigung dünner Aluminium‐Zirkonium‐Folien durch Magnetron‐Sputtern. Issue 11 (17th November 2016) - Egorova, A.; Kovac, J.; v. Hehl, A.; Mehner, A.; Zoch, H.‐W.
Abstract : In the foregoing years, micro components were frequently employed in various sectors such as the electronics and medical industry. In order to produce these components in large amounts and satisfying quality, the production processes have to be improved constantly. Heat treatment represents a critical step in the production chain of micro components, since it can either soften the foils for micro forming or increase the hardness of the micro components after the cold forming process, provided those are made of hardenable materials. In the investigated Al–Zr alloy, the formation of small primary Al3 Zr precipitations results in a considerable improvement of the material's hardness. However, the presence of precipitations in the Al–Zr foils drastically limits the formability. Additionally, the precipitations are nearly not avoidable in the casting of the raw material and irreversible due to the limited solubility of zirconium in aluminum (0.28 wt%) close to the melting point of the aluminum solution. To overcome this problem, magnetron sputtering was employed to fabricate zirconium supersaturated Al–Zr foils by taking advantage of a low substrate temperature (below 50 °C). In particular the plasma power seems to influence the aging behaviour of sputtered Al–Zr foils.